2003
DOI: 10.1074/jbc.m212421200
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine Acts as an Anti-hemostatic Molecule in the Saliva of the Blood-sucking Bug Rhodnius prolixus

Abstract: Blood-sucking arthropods possess a variety of antihemostatic factors in their salivary glands to maintain blood fluidity during feeding. In this work we demonstrate the anti-hemostatic properties of lysophosphatidylcholine (lysoPC) isolated from the salivary glands of Rhodnius prolixus. First, we examined salivary glands of fourth and fifth instar nymphs for their phospholipid composition. The lumen displayed an accumulation of its phospholipid content, mainly phosphatidylcholine and lysoPC, with a 6-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Among other activities, LPC is known to be a powerful modulator of endothelium-dependent arterial relaxation (Kugiyama et al, 1990). We showed that it is present in the saliva of a blood-sucking insect, R. prolixus, one of the main vectors of Chagas disease in South America (Golodne et al, 2003). In addition, we showed that it might act as an antihemostatic molecule during blood feeding, by blocking platelet aggregation and inducing NO production in cultured endothelial cells.…”
mentioning
confidence: 87%
“…Among other activities, LPC is known to be a powerful modulator of endothelium-dependent arterial relaxation (Kugiyama et al, 1990). We showed that it is present in the saliva of a blood-sucking insect, R. prolixus, one of the main vectors of Chagas disease in South America (Golodne et al, 2003). In addition, we showed that it might act as an antihemostatic molecule during blood feeding, by blocking platelet aggregation and inducing NO production in cultured endothelial cells.…”
mentioning
confidence: 87%
“…Despite the fact that two bugderived biological fluids (feces and saliva) are inoculated into the bite wound, no vector-derived molecules have been described as playing a role in the mechanism of T. cruzi infection of vertebrate hosts. Previously, we demonstrated the presence of phospholipids in the saliva of a blood-sucking insect, Rhodnius prolixus, one of the main vectors of Chagas disease in South America (24). Also in that study, we showed that lysophosphatidylcholine (LPC) is a component of this insect's salivary secretion and may act as an antihemostatic molecule during blood feeding.…”
mentioning
confidence: 87%
“…LPC was obtained by the extraction of total lipids from salivary glands and feces. It was purified by thin-layer chromatography as described previously (24). R. prolixus LPC from saliva is henceforth designated RpLPC.…”
Section: Methodsmentioning
confidence: 99%
“…Both of these products are important signaling molecules. We have shown the presence of lysophospholipids, mainly lysophosphatidylcholine (LPC), in the saliva and feces of R. prolixus [57,58]. LPC acts as a chemotactic molecule for monocytes and macrophages, but also plays a role in the production of NO by these cells, therefore enhancing T. cruzi infection through immunosuppression.…”
Section: Introductionmentioning
confidence: 99%